Location based social networks: definition, current state of the art and research agenda - Roick, Oliver; Heuser, Susanne (Transactions in GIS, 2013)
The growing penetration of GPS equipped smartphones allowing users to constantly share geographic information on their current whereabouts has led the way to an augmentation of existing Social Network Sites with location-based features or the creation of new ones exclusively around geographic information. Within these Location Based Social Networks vast amounts of geographic information are allocated, which attracted the attention of researchers with various scientific backgrounds. This article presents a comprehensive definition of this special type of Social Network Site and an overview of research activities, which are currently conducted using the data. Finally, a research agenda for GIScience is drawn from existing research directions.
Gesehen am 19.01.2022